Evaluación basal integral de las condiciones de salud física y visual en adultas mayores (2022)
The purpose of this article is to describe the physical and visual health conditions of physically active older women. It is a quantitative, observational, descriptive cross-sectional study with women over 60 years of age belonging to the group of older adults of the Universidad Santo Tomás of Bucaramanga. Visual acuity, physical qualities and risk of falling were evaluated. The data were organized, cleansed in Excel and validated in EpiData. The analysis was carried out taking into account the nature and distribution of the data of 33 women, with an average age of 68 years. Ninety-three point ninety-four percent (93.94%) were obese. They presented normal values ​​for aerobic endurance, lower and upper limb strength. Of the participants, 90.90% had visual acuity between 20/20 and 20/40, with an average stereopsis of 49.47 arc seconds. No statistically significant dependence is evident when relating visual acuity and stereopsis to women’s performance in the obstacle course test. Good eye health and visual acuity reduce the risk of falls. A good physical condition represents a minimal risk of falling, therefore, it is relevant to generate interdisciplinary training plans that allow the maintenance of the physical and visual functions of older adults.